A Multimodal Analysis of Low-Quality Content on TikTok and Its Impact on the Resilience of Children and Adolescents in Indonesia - Ayunda Putri Wijaya; Dilla Atqia Rahmah; Shabrina Fidinil Haq; Wanda Rahmawati Azahra; Indra Sarathan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The increasingly popular social media platform TikTok in several countries contains various types of content, ranging from educational to entertainment content. There is also low-quality content that can have a negative impact on TikTok users. This study aims to examine indicators of low-quality content, such as the TikTok trend Joget Tembak Dor Dor Dor, and describe its impact on the resilience of children and adolescents. This study uses descriptive analysis with multimodal theory. The data collection techniques used are observation and interviews. The results show that indicators of low-quality content are found in both verbal and written language and in the visualization of the content. This low-quality content can affect children's resilience, especially in facing academic problems and challenges. In conclusion, indicators of low-quality content can be identified through language and visual aspects. To minimize children's consumption of low-quality content, parents need to be involved in implementing the proposed solutions.